Health care utilisation in treatment-resistant depression: a Swedish population-based cohort study. (1st September 2022) - Brenner, Philip; Nygren, Adam; Hägg, David; Tiger, Mikael; O'Hara, Marguerite; Brandt, Lena; Reutfors, Johan
Abstract: Objective: To investigate the health care utilisation (HCU) among patients with treatment-resistant depression (TRD) compared to patients with depression not meeting TRD criteria. Methods: Nationwide Swedish registers were used to identify patients 18–69 years old with incident depression and antidepressant treatment. Patients were followed prospectively and defined as having TRD at start of the third distinct consecutive treatment episode. Each of the 16, 329 identified TRD patients were matched with five comparators with depression not meeting criteria for TRD. Main outcome measure was total number of inpatient days and outpatient visits, and secondary outcome was HCU in connection with a main diagnosis of depression or suicide attempt. Results: TRD patients had a significantly higher risk of all-cause inpatient care than comparators (first year adjusted risk ratio [aRR] 3.03 [95%CI 3.01–3.05], years 1–3 aRR 2.15 [2.13–2.16]). This was more pronounced when the main diagnosis was depression (first year aRR 4.41 [4.36–4.45]), and after suicide attempt (first year aRR 4.43 [4.26–4.60]). Outpatient visits were also markedly more frequent for patients with TRD (first year aRR 2.05 [2.03–2.07]). Higher HCU among TRD patients persisted throughout follow-up. Conclusions: Patients with TRD may have a twofold to fourfold higher HCU than other patients with depression. KEYPOINTS: This register-based prospective study investigated health care utilisation (HCU) among patients with treatment-resistant depression (TRD) compared to other patients with depression. Patients with TRD had a two to fourfold higher HCU regarding all measured outcomes, including inpatient hospital days and outpatient visits. The elevated HCU persisted for more than three years, although decreasing gradually. This should correspond to increased costs and individual burden for patients with TRD.